Exploring The Experience of Mothers of Premature Babies: A Phenomenological Study: Experience of Mothers of Premature Babi - Gulshan, Sobia; Ozigi Abdullahi, Kabir; Yaqoob, Adnan; Ali, Afsar (Pakistan Journal of Health Sciences, 2023)
Premature birth of babies is a one of the major public health problems all around the world. Objective: To explore the experience of mothers of preterm babies when their baby is admitted in a tertiary care hospital of Lahore. Methods: This study was conducted in the Neonatology department of Children’s Hospital, Lahore, Tertiary Care Hospital, Pakistan from June 2022 to December 2022. Semi structured face-to-face individual interview was used to obtain data from the 12 participants who were purposively selected for the study. The audio recorded data collected was translated into English and transcribed verbatim. Analysis was done with the help of computer assisted software called NVIVO-12. By using the Coliazzi’s method of phenomenological analysis the codes generated from NVIVO-12 were organized into sub-categories, categories, sub-themes and themes. Results: Three themes emerged with sixteen subthemes. The themes are: Mixed emotional feelings of the mothers; Mother’s satisfaction about care and support from Health Care Professionals; Mother-baby interaction in NICU. Mothers were worried due to unexpected emergency premature delivery and baby’s status and had uncertainty related to delivery outcome and the baby’s life. Participants have good interaction babies while the Kangaroo Mother Care and Breast Feeding and they applaud HCPs. Conclusions: Mothers were concerned about the survival of premature babies admitted to the NICU. They showed different emotions like fear, anger, sadness, worry, tension, lack of confidence, hope, gratefulness, courage and spiritual faith in Allah. They expressed the feelings of satisfaction about care, treatment counseling and teaching by HCPs.